Sizing and operation co‐optimization strategy for flexible traction power supply system. Issue 6 (16th March 2023) - Zhang, Shanshan; Yang, Shaobing; Liu, Qiujiang; Hu, Bin; Zhang, Junting; Guerrero, Josep
Abstract: Dispatchable energy storage system (ESS) plays a critical role in the smart grid through energy shift and power support. However, it exhibits different operational strategies and economic benefits in different application scenarios due to its inherent degradation behaviour. This paper aims to explore the technical and economic feasibility of the flexible traction power supply system (FTPSS) integrating ESS and renewable energy sources (RES) based on the traction load characteristics. First, a battery degradation model applicable in its frequent charging and discharging operating conditions is derived. Then this paper develops an operational‐sizing co‐optimization framework for the ESS in the FTPSS, where the operation decisions are made considering the degradation costs varying with the sizes and energy throughput. To solve this large‐scale non‐linear intertemporal decision‐making problem, an iterative method with a linear programming (LP) core is proposed to achieve the trade‐off between computational efficiency and accuracy. The results of the extensive comparative cases show that the proposed approach can achieve approximately 10% higher economic benefits than the existing bi‐level sizing strategies for FTPSS.